Pengaturan Pelaksanaan Pemilihan Kepala Daerah Serentak - Nazriyah, R. (Jurnal Hukum IUS QUIA IUSTUM, 2016)
The issues to be examined in this research is how does the practice of simultaneous Local Election according to the valid legislation and which institution is authorized to settle the disputes of simultaneous local elections? This research is normative. The study found that Article 3 (1) regulation number 1 2014 About the Election of governors, regents and mayors passed into law No. 1 Year 2015 on the Election of governors, regents, and the Mayor state that, the local election is held every 5 (five) years simultaneously throughout the territory of the Republic of Indonesia.The Local Election schedule is implemented in several periods. Meanwhile the simultaneous national elections is held in 2027. Law No. 1 2015 mandates the Constitutional Court to resolve the dispute over the local elections, despite the fact that it is unlikely for one institution to examine and judge hundreds of cases of disputed local elections at the same time. Local Election dispute resolution processes also have a specified time limit. To that end, the institutions considered most appropriate to handle election disputes is the Supreme Court by delegating the High Court in each region. If litigants are not satisfied with the decision of the High Court then, they may appeal to the Supreme Court.